The Imagery of Death in the Visual Discourse of French Illumination of the 13th-15th Centuries: Iconographic Typologies and Artistic Practice - Hrynda, Bohdana; Tkachuk, Ilona; Lysun, Yaryna; Shymin, Yaroslav; Odrekhivskyi, Vasyl (Convergences - Journal of Research and Arts Education, 2024)
Classical historical and art studies in the context of the development of modern humanities are frequently synthesised with research on visual culture and social art history, forming a broad discourse on the study of the culture of a particular era, country, or community. This optics is taken as the basis for this study, wherein such a fundamental philosophical concept as the attitude towards death is considered from the standpoint of art history iconographic and cultural studies to identify worldviews and ideology in the development of visual narratives that cover and represent them. In this dimension, illuminated manuscripts are the research subject and object where, through the synthesis of text and image, the ability to semiotically read images and decode the symbolic content of cultural categories opens up wide interpretative possibilities for the researcher. The purpose of this study is to outline the wide variability of iconographic typologies associated with the theme of death in the late medieval European culture of the Latin West and to cover the features of the connection of visual culture with the system of worldview representations based on symbolism rooted in religion, folklore, and court aristocratic culture. The proposed study uses an interdisciplinary scientific approach and an art history approach. The research is based on the methods of stylistic and formal analysis, semiotics, and hermeneutics. The typological approach allowed identifying groups of images united by identical semantics of image interpretation, joint compositional and plot solutions designed to accessibly decode their semantics. First, the ontological and metaphysical foundations of the perception of death as a phenomenon in the philosophical and anthropological dimension in culture in general, and in western European culture in particular, are defined and characterised. In the context of the analysis of the features of the symbolic and iconographic interpretation of images of death in the visual culture of illumination of the 13th-15th centuries, groups of images are identified, united by identical semantics of interpretation of these images, joint compositional and plot solutions designed to accessibly decode their semantics, namely the imagery of the death of saints and clergy, imagery of the death of monarchs, the death of soldiers, noble chivalry, the death of fallen in battle, the death of women, imagery of suicides, as well as imagery of violent death, murder. This study covers a wide range of potential recipients in modern humanitarianism and can be useful for historians, medievalists, art historians, anthropologists, and cultural scientists.